Allosteric Regulation of 3CL Protease of SARS-CoV-2 and SARS-CoV Observed in the Crystal Structure Ensemble. Issue 24 (3rd December 2021) - Kidera, Akinori; Moritsugu, Kei; Ekimoto, Toru; Ikeguchi, Mitsunori
Graphical abstract: Highlights: Dynamics of SARS-CoV/SARS-CoV-2 3CLpro was analyzed using 184 crystal structures. Dynamics was identified as the motions of the four flexible loops and the domain III. The catalytic activity is regulated by five hydrogen bonds with the catalytic loop. Ligand binding causes a ligand size dependent conformational change to the two loops. Mutation T285A between the two coronaviruses affects both structure and activity. Abstract: The 3C-like protease (3CL pro ) of SARS-CoV-2 is a potential therapeutic target for COVID-19. Importantly, it has an abundance of structural information solved as a complex with various drug candidate compounds. Collecting these crystal structures (83 Protein Data Bank (PDB) entries) together with those of the highly homologous 3CL pro of SARS-CoV (101 PDB entries), we constructed the crystal structure ensemble of 3CL pro to analyze the dynamic regulation of its catalytic function. The structural dynamics of the 3CL pro dimer observed in the ensemble were characterized by the motions of four separate loops (the C-loop, E-loop, H-loop, and Linker) and the C-terminal domain III on the rigid core of the chymotrypsin fold. Among the four moving loops, the C-loop (also known as the oxyanion binding loop) causes the order (active)–disorder (collapsed) transition, which is regulated cooperatively by five hydrogen bonds made with the surrounding residues. The C-loop, E-loop, and Linker constitute the major ligand binding sites, which consist of a limited variety of binding residues including the substrate binding subsites. Ligand binding causes a ligand size dependent conformational change to the E-loop and Linker, which further stabilize the C-loop via the hydrogen bond between the C-loop and E-loop. The T285A mutation from SARS-CoV 3CL pro to SARS-CoV-2 3CL pro significantly closes the interface of the domain III dimer and allosterically stabilizes the active conformation of the C-loop via hydrogen bonds with Ser1 and Gly2; thus, SARS-CoV-2 3CL pro seems to have increased activity relative to that of SARS-CoV 3CL pro .